The Influence Of Work Facilities And Work Motivation On Employee Performance In The Manpower Office Of North Sumatra Province - Nasution, Ade Ariska; Darmilisani, Darmilisani; Arifin , Daud (Journal of Management, Economic, and Accounting, 2026)
The research analysis aims to determine the influence of work facilities and work motivation on employee performance at the North Sumatra Provincial Manpower Office. The research approach used is associative and quantitative. This study employed multiple linear regression analysis. The sample in this study consisted of 47 respondents. Primary data collection used a questionnaire. The results of the study showed that the t count value was 3.475 and the t table was 2.015368, so the t count > t table (3.475 > 2.015368) with sig. 0.001 < 0.05 so that the results of the study accepted H1. It can be explained that the work facilities variable (X1) has an effect on the employee performance variable (Y). The test results showed a t count value of 6.364 and the t table of 2.015368, so the t count > t table (6.364 > 2.015368) with sig. 0.000 < 0.05 so that the results of the study accepted H2. It can be explained that the work motivation variable (X2) has an effect on employee performance (Y). The test results showed the ft table value at a significant confidence level of 0.05 was 3.20, thus the results of the SPSS calculation obtained f count = 31.911 > ft table 3.20 with sig. 0.000 < 0.05. Therefore, it can be concluded that H3 is accepted. Where the variables of work facilities (X1) and work motivation (X2) simultaneously have a positive and significant effect on the performance of employees of the North Sumatra Provincial Manpower Office.